STUDI TENTANG MODEL HIDROGRAF SATUAN SINTETIK PADA SUB DAS BAYUR SAMARINDA, KALIMANTAN TIMUR - Syafrudin, Muhammad (Indonesia University of Education, 2008)
The present research entitled Study of Synthetic Unit Hydrograph Model of Bayur River Basin at Samarinda, East Kalimantan was aimed to analyze and identify the best-suited synthetic unit hydrograph to apply in Bayur river basin. The research was carried out by developing models, and then those models were compared to main unit hydrograph based on 2004 field measurement. Comparative analysis was performed on two stages. The first was to calculate and compare three-unit hydrograph parameters (Tp, Qp and Tb) of two synthetic unit hydrograph to main unit hydrograph. Second stage was to develop direct runoff hydrograph of two synthetic unit hydrograph models and of the main unit hydrograph using rainfall data of April 9, 2004. Then, deviation percentage averages of the two synthetic direct runoff hydrograph were calculated. Through the two analysis stages, the best-suited synthetic unit hydrograph model to apply in Bayur river basin presumably was obtained by identifying smallest deviation percentage average on main unit hydrograph. By calculating deviation averages of direct runoff hydrograph in the two models of synthetic unit hydrograph, it was found that GAMA I model provided smallest deviation average compared Snyder model. Based on the two analysis, it was showed that GAMA I was the closest model to main unit hydrograph compared to Snyder model.Key word: synthetic unit hydrograph, river basin, direct runoff, Snyder model, GAMA I model.